CHARACTERISTICS OF SUCCESSFUL LOCAL BLENDED PROGRAMS IN THE CONTEXT OF THE SLOAN-C PILLARS - Moloney, Jacqueline F.; Hickey, Charmaine P.; Bergin, Amy L.; Boccia, Judith; Polley, Kathleen; Riley, Jeannette E. (Online Learning, 2010)
Drawing on the University of Massachusetts experience in developing successful blended local programs, this paper suggests guiding principles that include mission-driven responsiveness to local contexts and partnerships; using low-cost marketing strategies available through local relationships and brand; attending to students’ preferences for blending face-to-face and online services and instruction throughout the college experience; supporting faculty in working with partners to develop local blended programs; and providing activities that anchor students to the campus and program.